Can transfers and behavior change communication reduce intimate partner violence four years post-program? Experimental evidence from Bangladesh - Roy, Shalini; Hidrobo, Melissa; Hoddinott, John F.; Koch, Bastien; Ahmed, Akhter (International Food Policy Research Institute, 2019)
Little is known about whether reductions in intimate partner violence (IPV) from cash transfer programs persist over the longer term. Using a randomized controlled trial design, we show that a program providing poor women in rural Bangladesh with cash or food transfers, alongside nutrition behavior change communication (BCC), led to sustained reductions in IPV 4 years after the program ended. Transfers alone showed no sustained impacts on IPV. Evidence suggests cash and BCC led to more sustained impacts on IPV than food and BCC – through persistent increases in women’s bargaining power, men’s costs of perpetrating violence, and poverty-related emotional well-being.